Efficiency of Islamic Rural Banks in Indonesia : A Non-Parametric Analysis - Arif Rahman, Hakim; Rossazana, Ab. Rahim (Human Resource Management Academic Research Society (HRMARS), 2025)
This research examines the technical efficiency of prominent Islamic microfinance working in Indonesia as the Islamic Rural Banks (IRBs) not only play their role in poverty alleviation but also become an essential stakeholder that becomes a cause of generating income activities in Indonesia through the provision of micro-financing to unbanked people. A non-parametric approach (Data Envelopment Analysis Techniques) was applied to observe the efficiency of 144 Decision-making Units (DMUs) in 21 provinces from 2012-2021. The results show only 12 exhibited notably high-efficiency levels. Those with lower efficiency levels demonstrated reduced Technical Efficiency (TE) and Pure Technical Efficiency (PTE), often attributed to deficient management, inadequate human resource quality, and insufficient funding. Geographic conditions highlight varying efficiency scores across provinces, with higher concentrations of IRBs in cities correlating with greater utilization potential and improved institutional performance.